Estratégias lúdicas para a recepção de crianças em centro cirúrgico - Garcia, Marla Andreia; Fernandes, Tatiana Roberta; Braga, Eliana Mara [UNESP]; Caldeira, Silvia Maria (My University, 2011)
This study aimed at learning about the nursing team's perception concerning the use of ludic strategies to receive children in the Surgery Suite (SS) of a university hospital. It is cross-sectional field study using qualitative methodology in which the nursing team answered a questionnaire addressing the use of ludic strategies in the perioperative period. All the respondents considered it to be important to use ludic strategies as they believed that they can reduce fear of the unknown, stress during the perioperative period as well as approximate children to their families and the surgery team. It was concluded that the nursing team presents a positive perception concerningthe use of ludic strategies and that they benefit children during the preoperative period, their mothers, who feel calmer when they see their offspring playing, as well as the nursing team, whose members face less resistance from the children when performing procedures.

El objetivo de este estudio fue conocer la percepción del equipo de enfermería a respecto de la utilización de estrategias lúdicas para niños en la recepción de la unidad del Bloque Quirúrgico (BQ) de un hospital universitario. Fue una investigación transversal, de campo, con metodología cualitativa. Todos los entrevistados consideraron importante la utilización de las estrategias lúdicas, pues creen que disminuyen el miedo a lo desconocido, reducen el estrés en el perioperatorio y acercan el niño y la familia al equipo de cirurgía. Concluimos que el equipo de enfermería presenta una percepción positiva cuanto a la utilización de las estrategias lúdicas y cuanto a los beneficios de la utilización para el niño en el perioperatorio, para la madre, quien se siente más tranquila al ver al hijo jugando, y para el propio equipo y que los niños ofrecen menos resistencia a la realización de los procedimientos.

O objetivo deste estudo foi conhecer a percepção da equipe de enfermagem a respeito da utilização de estratégias lúdicas para crianças na recepção da unidade de Centro Cirúrgico (CC) de um hospital escola. Foi uma pesquisa transversal, de campo, com metodologia quanti-qualitativa, na qual a equipe de enfermagem respondeu um questionário quanto à utilização das estratégias lúdicas no perioperatório. Todos os entrevistados consideraram importante a utilização das estratégias lúdicas, pois diminuem o medo do desconhecido, reduzem o estresse no perioperatório e aproximam a criança e a família da equipe de cirurgia. Concluímos que a equipe de enfermagem apresenta uma percepção positiva quanto à utilização de estratégias lúdicas e que os benefícios da utilização são para a criança no perioperatório, para a mãe que se sente mais tranquila ao ver o filho brincando e para a própria equipe que apresenta menor resistência por parte das crianças na realização dos procedimentos.
Ludic strategies to receive children in the surgery suite
Estrategias lúdicas para la recepción de niños en bloque quirúrgico
Keywords: Child; Nursing team; Communication; Toy; Niño; Equipo de enfermería; Comunicación; Juguete; Criança; Equipe de enfermagem; Comunicação; Brinquedo